PERCEPTION OF DAIRY FARMERS TOWARDS ATTRIBUTES OF DAIRY INNOVATIONS IN NORTH INDIA - Rathod, Prakash Kumar; Chander, Mahesh (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
An ex-post-facto exploratory study was carried out in four Indian States with the specific objective to know the perception of dairy farmers towards attributes of five identified dairy innovations of socio economic importance. Concentrate feeding, artificial insemination (AI), vaccination, clean milk production (CMP) and use of mobiles in dairying were the innovations of the study. It was found that majority of the farmers across all states had medium level of favourable perception for all the dairy innovations. However, proportion of farmers with high level of favourable perception was seen among the farmers of Haryana and Punjab. Highly significant difference (p< 0.01) in terms of perception of farmers towards attributes of innovations across the states was observed. This might be due to variations in socio-economic and psychological characteristics of the respondents across the states. The study thus concludes that, attributes of dairy innovations must be duly considered for effective diffusion and adoption leading to improved quality and productivity in Indian dairy sector.